Evaluasi Kegiatan Konseling Dan Tes Hiv Sukarela (KTS) di Puskesmas Wilayah Jakarta Timur Tahun 2014 - Nauri Anggita Temesvari (Indonesian of Health Information Management Journal (INOHIM), 2015)
Abstract HIV Voluntary Counseling and Testing (VCT) is the entry point of preventing HIV/AIDS. East Jakarta targeted 20.308 of key population could visited VCT in 2013, but it’s just reached 67%. Thus, as researcher i would like to evaluate the implementation of VCT in Primary Health care (Puskesmas) in East Jakarta Area. Tool which is used in this research is Logical Framework Analysis (LFA). LFA evaluate VCT from input (fund, health worker, policy, and facility), activity (health worker’s training, counseling and tesing program, and monitoring evaluation), and output (total trained health worker, client satisfaction, councelor satisfaction) of VCT. Client and health worker were interviewed to confirm what they expect and what they get from VCT. The result is overall implementation of VCT has gone well. However, the lack of awareness of key populations to visit healthcare centre as early as possible, the lack of accurate data collection, and the lack of socialization to the general population compared to key populations are the barriers of the implementation. Recommendations from this research are to improve outreach of key population; include in the community, to monitor all of data recording and reporting, and to improve the function of primary healthcare as Sustainable Comprehensive Services (LKB).Keywords: HIV, VCT, LFAAbstrakKonseling dan Tes HIV Sukarela (KTS) merupakan pintu masuk dalam pencegahan HIV/AIDS. Jakarta Timur menargetkan seluruh populasi kunci yang memanfaatkan KTS sebesar 20.308 orang. Namun, yang baru tercapai pada tahun 2013 sebesar 67%. Oleh karena itu, dalam penelitian ini dilakukan evaluasi dengan Kerangka Kerja Logis untuk melihat pelaksanaan KTS yang telah berjalan. Dari hasil penelitian didapat bahwa keseluruhan pelaksanaan KTS telah berjalan dengan baik, kurangnya kesadaran dari populasi kunci untuk memeriksakan diri sedini mungkin, kurang akuratnya pengumpulan data, dan kurangnya sosialisasi ke populasi umum dibandingkan dengan populasi kunci menjadi permasalahan utama dalam pelaksanaan KTS. Rekomendasi dari penelitian ini adalah meningkatkan penjangkauan ke lokasi yang memungkinkan populasi kunci tersebar, termasuk di lingkungan masyarakat, pengawasan dalam pencatatan dan pelaporan, dan meningkatkan fungsi Puskesmas dalam Layanan Komprehensif Berkesinambungan (LKB).Kata kunci: KTS, HIV, KKL